The scent of rain & lightning [videorecording (DVD)]. - Monroe, Maika; Webber, Mark, 1980-; Patton, Will; Bedelia, Bonnie, 1946- (Echo Bridge Acquisition Corp. LLC, 2018)
When the man convicted of killing her parents has his sentence pardoned, Jody, a Midwestern twenty-something, begins to question the facts behind her parents' deaths and gradually faces the possibility that the wrong man was convicted of the crime. The further Jody delves into the past, she is forced to revisit old wounds.